A Comparative Study of High-Temperature Latent Heat Storage Systems - Alok Kumar Ray (MDPI AG, 2021)
High-temperature latent heat storage (LHS) systems using a high-temperature phase change medium (PCM) could be a potential solution for providing dispatchable energy from concentrated solar power (CSP) systems and for storing surplus energy from photovoltaic and wind power. In addition, ultra-high-temperature (>900 °C) latent heat storage (LHS) can provide significant energy storage density and can convert thermal energy to both heat and electric power efficiently. In this context, a 2D heat transfer analysis is performed to capture the thermo-fluidic behavior during melting and solidification of ultra-high-temperature silicon in rectangular domains for different aspect ratios (AR) and heat flux. Fixed domain effective heat capacity formulation has been deployed to numerically model the phase change process using the finite element method (FEM)-based COMSOL Multiphysics. The influence of orientation of geometry and heat flux magnitude on charging and discharge performance has been evaluated. The charging efficiency of the silicon domain is found to decrease with the increase in heat flux. The charging performance of the silicon domain is compared with high-temperature LHS domain containing state of the art salt-based PCM (NaNO3) for aspect ratio (AR) = 1. The charging rate of the NaNO3 domain is observed to be significantly higher compared to the silicon domain of AR = 1, despite having lower thermal diffusivity. However, energy storage density (J/kg) and energy storage rate (J/kgs) for the silicon domain are 1.83 and 2 times more than they are for the NaNO3 domain, respectively, after 3.5 h. An unconventional counterclockwise circular flow is observed in molten silicon, whereas a clockwise circular flow is observed in molten NaNO3 during charging. The present study establishes silicon as a potential PCM for designing an ultra-high-temperature LHS system.